Butyrate modifies intestinal barrier function in IPEC-J2 cells through a selective upregulation of tight junction proteins and activation of the Akt signaling pathway - Yan, Hui (PLoS One, 2017)
The intestinal epithelial barrier, composed of epithelial cells, tight junction proteins and intestinal secretions, prevents passage of luminal substances and antigens through the paracellular space. Dysfunction of the intestinal barrier integrity induced by toxins and pathogens is associated with a variety of gastrointestinal disorders and diseases. Although butyrate is known to enhance intestinal health, its role in the protection of intestinal barrier function is poorly characterized. Therefore, we investigated the effect of butyrate on intestinal epithelial integrity and tight junction permeability in a model of LPS-induced inflammation in IPEC-J2 cells. Butyrate dose-dependently reduced LPS impairment of intestinal barrier integrity and tight junction permeability, measured by trans-epithelial electrical resistance (TEER) and paracellular uptake of fluorescein isothiocyanate-dextran (FITC-dextran). Additionally, butyrate increased both mRNA expression and protein abundance of claudins-3 and 4, and influenced intracellular ATP concentration in a dose-dependent manner. Furthermore, butyrate prevented the downregulation of Akt and 4E-BP1 phosphorylation by LPS, indicating that butyrate might enhance tight junction protein abundance through mechanisms that included activation of Akt/mTOR mediated protein synthesis. The regulation of AMPK activity and intracellular ATP level by butyrate indicates that butyrate might regulate energy status of the cell, perhaps by serving as a nutrient substrate for ATP synthesis, to support intestinal epithelial barrier tight junction protein abundance. Our findings suggest that butyrate might protect epithelial cells from LPS-induced impairment of barrier integrity through an increase in the synthesis of tight junction proteins, and perhaps regulation of energy homeostasis.